A Highly Active Molybdenum Phosphide Catalyst for Methanol Synthesis from CO and CO2. (18th October 2018) - Duyar, Melis S.; Tsai, Charlie; Snider, Jonathan L.; Singh, Joseph A.; Gallo, Alessandro; Yoo, Jong Suk; Medford, Andrew J.; Abild‐Pedersen, Frank; Studt, Felix; Kibsgaard, Jakob; Bent, Stacey F.; Nørskov, Jens K.; et al.
Abstract: Methanol is a major fuel and chemical feedstock currently produced from syngas, a CO/CO2 /H2 mixture. Herein we identify formate binding strength as a key parameter limiting the activity and stability of known catalysts for methanol synthesis in the presence of CO2 . We present a molybdenum phosphide catalyst for CO and CO2 reduction to methanol, which through a weaker interaction with formate, can improve the activity and stability of methanol synthesis catalysts in a wide range of CO/CO2 /H2 feeds.